Low serum potassium concentration is a predictor of chronic kidney disease. Issue 6 (20th February 2014) - Fukui, M.; Tanaka, M.; Toda, H.; Asano, M.; Yamazaki, M.; Hasegawa, G.; Nakamura, N.
Summary Aims The aim of this study was to examine whether low serum potassium concentration could be a predictor of chronic kidney disease (CKD) in a community‐based cohort. Materials and methods We enrolled 1001 subjects, median period of 5.7 years, and evaluated the risk factors for CKD, defined as estimated glomerular filtration rate (eGFR) < 60 ml/min/1.73 m2, and assessed whether low serum potassium concentration could predict CKD. Results Compared with the subjects without development of CKD, age, body mass index, fasting plasma glucose, uric acid (UA), creatinine and serum sodium concentration were higher, and serum potassium concentration was lower in subjects with development of CKD. Univariate Cox regression analyses demonstrated that age, body mass index, fasting plasma glucose, UA, creatinine, serum sodium concentration and serum potassium concentration were associated with progression of CKD. Multiple Cox regression analysis revealed that age, gender, creatinine and serum potassium concentration were independent predictors of CKD after adjustment for covariates. When serum potassium concentration was below 4.0 mmol/l at baseline, hazard ratio (95% confidence interval) of developing CKD was 2.65 (2.04–3.44; p < 0.0001). Conclusions Serum potassium concentration could be a clinically relevant risk factor for the progression of CKD, defined as eGFR < 60 ml/min/1.73 m2, in healthy subjects.